Clinical Holistic Medicine: A Pilot Study on HIV and Quality of Life and a Suggested Cure for HIV and AIDS - Søren Ventegodt; Trine Flensborg-Madsen; Niels Jørgen Andersen; Mohammed Morad; Joav Merrick (The Scientific World Journal)
This study was undertaken to examine the association between the immunological impact of HIV (measured by CD4 count) and global self-assessed quality of life (QOL) (measured with QOL1) for people suffering from HIV, to see if the connection was large and statistically strong enough to support our hypothesis of a strong QOL-immunological connection through the nonspecific, nonreceptor-mediated immune system, and thus to give a rationale for a holistic cure for HIV. This cross-sectional population study in Uganda included 20 HIV infected persons with no symptoms of AIDS and a CD4 count above 200 mill./liter. The main outcome measures were CD4 count, global QOL measured with the validated questionnaire QOL1, translated to Luganda and translated back to English. We found a large, clinically significant correlation between the number of T-helper cells (CD4) and global self-assessed quality of life (QOL1) (r = 0.57, p = 0.021), when controlled for age, gender, and years of infection. Together with other studies and holistic medicine theory, the results have given rationale for a holistic cure for HIV. We suggest, based on our findings and theoretical considerations, that HIV patients who improve their global QOL, also will improve their CD4 counts. Using the technique of holistic medicine based on the life mission theory and the holistic process theory of healing, we hypothesize that the improvement of QOL can have sufficient biological effect on the CD4, which could avoid or postpone the development of AIDS. A holistic HIV/AIDS cure improving the QOL draws on hidden resources in the person and is thus affordable for everybody. Improving global QOL also means a higher consciousness and a more ethical attitude, making it more difficult for the HIV-infected person to pass on the infection.